Factors that influence school attendance and participation in children and adolescents with juvenile idiopathic arthritis - a systematic review of the literature - Tom Spillane; Kieran Murray (Pediatric Rheumatology Online Journal)
Abstract Introduction Juvenile Idiopathic Arthritis (JIA) is an umbrella term for causes of inflammatory arthritis in children and adolescents. Symptoms include pain, stiffness and fatigue and this can have an impact on a child’s ability to attend school or participate in school activities, such as physical education. Methods Using Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) methodology, the research databases Pubmed, EMBASE and CINAHL were searched using key words related to JIA and school attendance and participation. Inclusion criteria were being 18 years old or under, having a diagnosis of JIA and examining JIA’s impact on either school attendance or participation in a school activity. Included studies were examined for factors that affected attendance or participation. Results Twelve research articles were included in the literature review. Six themes were identified as affecting attendance and participation. They were (1) Symptoms and treatment of JIA (2) Disability (3) Psychological symptoms (4) Disease activity and JIA subtype (5) Communication and school support and (6) Factors that increased participation. Conclusion Children and adolescents with JIA have reduced levels of school attendance and often cannot participate fully in school life due to their medical condition. Targeted strategies may improve participation rates in this population. Further research is needed in this area to develop interventions and strategies to facilitate the optimal educational and school experience possible for this cohort.